Banking liberalisation and corporate ESG performance: evidence from the removal of foreign ownership restrictions in China - Li, Yanzhen; Liu, Huixia; Guo, Zixun; Gao, Zhimei (Frontiers in Environmental Science, 2025)
IntroductionBanking liberalisation helps introduce international capital and environmental, social and governance (ESG) concepts and practices. Clarifying how this institutional policy promotes corporate ESG performance is crucial to sustainable development in emerging economies.MethodsBased on the exogenous policy shock of China’s removal of foreign ownership restrictions in the banking sector, the impact of banking liberalisation on corporate ESG performance is empirically tested using a generalised difference-in-differences (DID) model.ResultsThe findings reveal that corporate ESG performance significantly improved after foreign ownership restrictions were removed in the banking sector. This conclusion holds after endogeneity and robustness tests. Mechanism analysis indicates that banking liberalisation enhances corporate ESG performance by improving ESG information disclosure, alleviating financing constraints, and curbing managerial myopia. Heterogeneity analysis shows that this effect is particularly pronounced in heavily polluting industries and firms with high loan dependency. Further analysis demonstrates that public environmental concerns positively moderate the benefits of liberalisation. The ESG-enhancing effect of liberalisation is stronger when firms face greater environmental scrutiny. The ESG improvement resulting from banking sector liberalisation exhibits regional spillover effects, with neighbouring firms simultaneously improving their ESG performance.ConclusionThis study enriches research on the micro-level effects of financial liberalisation and provides important policy implications for emerging economies seeking to enhance corporate ESG performance.